2019
DOI: 10.1101/717579
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The unique topologies ofN6-Adenosine methylation (m6A) in land-plant mitochondria and their putative effects on organellar gene-expression

Abstract: Mitochondria are the main source of ATP production and also contribute to many other processes central to cellular function. Mitochondrial activities have been linked with growth, differentiation and aging. As relicts of bacterial endosymbionts, these organelles contain their own genetic system (i.e., mitogenome or mtDNA). The expression of the mtDNA in plants is complex, particularly at the posttranscriptional level. Following transcription, the polycistronic pre-RNAs in plant mitochondria are processed into … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 102 publications
1
9
0
Order By: Relevance
“…This finding is consistent with other experiments demonstrating the additive negative effect of multiple m 6 A residues on translation (Slobodin et al, 2017) and the depletion of m 6 A from efficiently expressed yeast and mammalian housekeeping genes (Schwartz et al, 2014). The negative correlation between methylated ORF and translation was observed in Xenopus embryos (Qi et al, 2016), maize (Luo et al, 2020), and in vitro tested plant mitochondrial transcripts (Murik et al, 2020), indicating an evolutionarily conserved effect. Indeed, the negative global relationship between the translation efficiency and m 6 A is apparent only when the latter is located within ORFs (Mao et al, 2019).…”
Section: Impact Of Transcription Elongation On Translationsupporting
confidence: 91%
“…This finding is consistent with other experiments demonstrating the additive negative effect of multiple m 6 A residues on translation (Slobodin et al, 2017) and the depletion of m 6 A from efficiently expressed yeast and mammalian housekeeping genes (Schwartz et al, 2014). The negative correlation between methylated ORF and translation was observed in Xenopus embryos (Qi et al, 2016), maize (Luo et al, 2020), and in vitro tested plant mitochondrial transcripts (Murik et al, 2020), indicating an evolutionarily conserved effect. Indeed, the negative global relationship between the translation efficiency and m 6 A is apparent only when the latter is located within ORFs (Mao et al, 2019).…”
Section: Impact Of Transcription Elongation On Translationsupporting
confidence: 91%
“…Accumulating evidence has indicated that dysregulation of m 6 A RNA methylation influences development in yeast (Yadav and Rajasekharan, 2017), meiosis in mice (Bushkin et al , 2019), fertility in Drosophila (Kan et al , 2017) and carcinogenesis in human cells (Dai et al , 2018; Pan et al , 2018). Recently, it has also been established that m 6 A methylation plays vital roles during the different stages of plant development, including embryo development (Bodi et al , 2012; Zhong et al , 2008), leaf morphogenesis (Arribas‐Hernández et al , 2018; Arribas‐Hernández et al , 2020; Růžička et al , 2017; Shen et al , 2016), trichome branching (Arribas‐Hernández et al , 2018; Bodi et al , 2012; Vespa et al , 2004; Wei et al , 2018), floral transition (Duan et al , 2017; Song et al , 2021), root growth (Chen et al , 2018; Růžička et al , 2017), the early degeneration of microspores in Oryza sativa (rice) (Zhang et al , 2019), fruit ripening in Solanum lycopersicum (tomato) (Zhou et al , 2019) and organellar gene expression (Murik et al , 2020). These findings clearly indicate that m 6 A RNA methylation plays crucial roles in the development of plants and animals.…”
Section: Introductionmentioning
confidence: 99%
“…While Arabidopsis serves as a prime model system for plant molecular genetics, cauliflower is employed for biochemical analysis of plant mitochondrial RNA metabolism (Grewe, et al 2014, Neuwirt, et al 2005, Sultan, et al 2016a. To generate the transcriptome maps of Arabidopsis and cauliflower mitochondria, we used total mtRNA extracted from highly enriched mitochondria preparations obtained from Arabidopsis seedlings and cauliflower inflorescence (Murik et al 2019). The mtRNA from each plant species was subjected to Illumina sequencing (see Materials and Methods), which resulted in approximately 6.2 million mapped reads for At-mtRNA (SRA no.…”
Section: Analysis Of the Mitochondrial Transcriptome Landscapes Of Armentioning
confidence: 99%
“…Mapping the Arabidopsis mtRNA-seq reads (SRA no. SRX4110179) (Murik, et al 2019) to mitochondrial genomic annotation and RT-qPCR data ( Figs. 1 and 2) demonstrated differential expression of the 21 mitochondria-encoded genes required for OXPHOS, as well as various ribosomal subunits (Fig 1c-e).…”
Section: Differential Expression Of Mitochondrial Genes In Arabidopsimentioning
confidence: 99%